RISK ASSESSMENT SYSTEM AFFECTING THE PRODUCTION PROCESS IN AGRICULTURE - Shamsieva Feruza Murathodjaevna; Fayzieva Nargiza Rabimovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this article, the risk assessment system affecting the production process in farms is presented. Agriculture is one of the most dangerous areas of entrepreneurial activity. This situation is influenced by many types of factors, in particular, the direct dependence of production on natural, climatic, weather and soil conditions, seasonality, the long duration of the capital turnover period, the difficulty of changing the field of activity, the process of introducing new techniques and technologies, and thoughts and opinions about other cases are given.